Artificial immune systems 10th International Conference, ICARIS 2011, Cambridge, UK, July 18-21, 2011. Proceedings - Liò, Pietro; Nicosia, Giuseppe; Stibor, Thomas (Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 10th International Conference on Artificial Immune Systems, ICARIS 2011, held in Cambridge, UK, in July 2011. The 37 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on immunoinformatics and computational immunology; theory of immunological computation; and applied immunological computation